Scientific capacity and industrial development as locomotors of international competitiveness in Latin America - Peña-Vinces, Jesús (2019)
Different bodies of literature emphasise the separate impact of the manufacturing sector and scientific capacity for competitiveness in developing countries. Scientific knowledge can increase productivity and promote innovation, while the manufacturing sector creates spillovers and generates processes of learning-by-doing. Yet, do these two processes complement each other? Do they, together, contribute to even higher international competitiveness? This paper explores these questions, drawing on an eleven-years panel data set for ten South American economies. We develop a moderation hypothesis model based on the congruence between science, industry, and international competitiveness. Our results support our hypothesis that scientific capacity and manufacturing development have a joint impact on international competitiveness that goes beyond their marginal effects and thus calls for future efforts to implement industrial policy.